Morphological and phylogenetic evidence reveal a new species of Protomerulius (Basidiomycota) from China - Gu, Zirui; Zhou, Chunqin; Deng, Qiaohua; Zhang, Jianling; Li, Mei; Zhou, Hongmin (Phytotaxa, 2025)
The corticioid fungi, distinguished by their longitudinally septate basidia, represent a unique group within the Auriculares taxa. A new corticioid fungus, Protomerulius wumengshanensis was discovered in Yunnan Province, southwest China, and is described and illustrated based on morphological and molecular evidence. It is characterized by producing white and smooth basidiomata, a monomitic system with clamp connections, hyphoid cystidia, longitudinally septate basidia, and thin-walled and oblong-ellipsoid, ellipsoid to ovoid, basidiospores measuring 4.3–5.9 × 3.0–4.0 µm. The new species resembles Protomerulius dubius macroscopically, but the latter differs in having larger basidiospores (5.2–8.0 × 3.7–4.7 μm vs. 4.3–5.9 × 3.0–4.0 μm). In nuclear large subunit rDNA (nLSU) and internal transcribed spacer (ITS) based phylogenies, the new species formed a distinct lineage in the Protomerulius clade. A full description, illustrations and phylogeny analysis results of the new species are provided.